TAHQIQUL AMAN MIN KHILALI TA’ZIZIL IMAN LI MU’ALAJATIT TATHARUF WAL IRHAB: DIRASAH SABIQAH LI FIKR AS-SYAIKH AFIFUDDIN MUHAJIR - Ibrahimy, Ach. Azaim; Amanullah, Muhammad; Zaim, Muntaha Artalim; Hendra, M. Yoeki (LP2M Universitas Ibrahimy, 2025)
The problem of extremism and terrorism is one of the most serious and pressing issues facing contemporary society. It has become an urgent concern for those interested in the state of religion. This study will address the role of faith in confronting extremism and terrorism, based on the ideas of Sheikh Afif al-Din Mahajir in his booklet, which remains unpublished. The research aims to analyze the concepts of faith and security in this ideology, reveal the mechanisms that link them in confronting extremism, and evaluate the effectiveness of this vision in addressing this problem. To our knowledge, this topic has not been addressed in previous studies. The research relied on an inductive and analytical approach to analyze Sheikh Afif al-Din Mahjar's thought. The research concludes that Sheikh Afif al-Din Mahjar's thought presents an integrated vision of the concepts of faith and security, and that this vision contributes effectively to countering extremism and terrorism by strengthening the relationship between the three sisterhoods (brotherhood of faith, Islamic brotherhood, and human brotherhood), strengthening social ties, and developing proper religious awareness and good deeds. Sheikh Afif al-Din Mahajir's thought is characterized by moderation and balance, rejecting extremism in all its forms and manifestations.